ANALISIS KETERLAKSANAAN PENDEKATAN SAINTIFIK BERDASARKAN KURIKULUM 2013 PADA MATA PELAJARAN FISIKA MENURUT PRESEPSI SISWA SMA NEGERI PEKANBARU - Ida Lisa; Mitri Irianti; M. Rahmad ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine the enforceability of the scientific approach is based on the curriculum in 2013 in physics according to student perception. The research is descriptive survey method. The population is students of class XI Science High School Pekanbaru, while the sample is a class XI student from the high school curriculum of 2013 for 3 consecutive years. Data collection instruments through the distribution of questionnaires. Results of research keterlaksanaan scientific approach in physics obtained an average score of 2.97 in the category quite well. It can be concluded that the application of the scientific approach to the learning process at schools with the maximum has not been done. It is caused by several factors, namely: the limited time, limited infrastructure such as infocus diruang classroom, the teacher is less a creative learning.Key Words: the nature of learning physics, curriculum in 2013, scientific approach